2020
DOI: 10.1016/j.jtherbio.2020.102660
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluating the wind cooling potential on outdoor thermal comfort in selected Iranian climate types

Abstract: Wind is one of the main factors affecting people's outdoor thermal sensation. Ongoing urbanization and urban densification are transforming the urban climate and complicating the pedestrian-level wind environment. Therefore, the main aim of this research is to evaluate the potential wind-cooling effect on human outdoor thermal conditions. Accordingly, the current research attempts determine the best wind directions for thermal comfort at the studied stations and how these factors will be changed under the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 59 publications
(67 reference statements)
2
12
0
Order By: Relevance
“…Perhaps one of the most important spatial contexts of recent climate warming has been in large urbanized areas. Here, heat islands have expanded spatially and become more intense due to the combined effects of both regional climate warming and enhanced urban warming through increased human-induced activities and land-cover change ( Huang & Lu, 2015 ; Roshan & Moghbel, 2020a ; Roshan, Moghbel, & Attia, 2020 ). In the context of Tehran, results indicate that the heat island has expanded over recent decades, most particularly in western and southwestern sectors where this coincides with originally vegetated surfaces having changed to areas now occupied by industrial development and extensive warehouse complexes.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps one of the most important spatial contexts of recent climate warming has been in large urbanized areas. Here, heat islands have expanded spatially and become more intense due to the combined effects of both regional climate warming and enhanced urban warming through increased human-induced activities and land-cover change ( Huang & Lu, 2015 ; Roshan & Moghbel, 2020a ; Roshan, Moghbel, & Attia, 2020 ). In the context of Tehran, results indicate that the heat island has expanded over recent decades, most particularly in western and southwestern sectors where this coincides with originally vegetated surfaces having changed to areas now occupied by industrial development and extensive warehouse complexes.…”
Section: Discussionmentioning
confidence: 99%
“…They found that the urban form had a significant effect on thermal comfort. Another study by Roshan et al [35] in 2020 evaluated the effect of potential wind cooling on the outdoor thermal condition of individuals in four different climatic types of Iran. One of these climates is Shiraz with a hot and semi-arid climate.…”
Section: Physical Parameters Of Streetscape Affecting Thermal Comfortmentioning
confidence: 99%
“…Due to rapid urbanization, the global population is migrating from rural to urban areas. This change is meanly observed during the previous few decades [1]. Therefore, cityinduced climate change has serious repercussions on public outdoor activities, health and tourism.…”
Section: Introductionmentioning
confidence: 97%